Design, Synthesis, and Biological Evaluation of Some Novel o-aminophenol Derivatives - Van Nguyen, Dat; Tran, Ly Duou; Vu, Phuong Uyen Ngoc; Van Meervelt, Luc; Nguyen, Mai Ngoc Thi; Ngo, Anh Lan; Duong, Hoan Quoc (Current Organic Synthesis, 2025)
Backgroundo-Aminophenol derivatives are of particular interest for their diverse biological activities and potential therapeutic applications. Such as, antioxidant, antibacterial, and cytotoxic activities.ObjectivesThis study aimed to design and synthesize a series of novel o-aminophenol derivatives through an efficient multi-step process, characterize them using modern spectroscopic techniques, and evaluate their antimicrobial, antioxidant, and cytotoxic activities.MethodsA series of novel derivatives of o-aminophenol have been successfully synthesized with very high efficiency through a simple six-step process using readily available chemicals and straightforward reactions. The structures of all products were accurately determined using modern spectroscopic methods such as 1D and 2D NMR, as well as IR, MS spectroscopy, and X-ray methods. The antimicrobial activities of eight o-nitrophenol derivatives were assessed against Gram (-) and Gram (+) bacteria as well as fungi. In comparison, antioxidant activities were tested for two o-nitrophenol and 11 o-aminophenol derivatives using SC50 and EC50 assays. Cytotoxicity was evaluated on KB, HepG2, A549, and MCF7 cancer cell lines.ResultsSix synthesized compounds 5b, 5c, 5g, 6b, 6c, 6g exhibited unusual doublet signals in the H8 region of the 1H NMR spectrum, attributed to atropisomer formation. Eight o-nitrophenol derivatives demonstrated weak antimicrobial activity, with MIC values ranging from 100 to 200 µg/mL. Compound 5g showed activity against all tested bacterial and fungal strains. In antioxidant testing, eight o-aminophenol derivatives 6a, 6b, 6c, 6e, 6f, 6h, 6i, and 12b displayed excellent activity, with SC50 values between 18.95 and 34.26 µg/mL, approaching ascorbic acid's SC50 value of 12.60 µg/mL. Three derivatives 6d, 6g, and 12a showed superior antioxidant activity with EC50 values between 4.00 and 11.25 µg/mL, surpassing quercetin's standard of 9.8 µg/mL. Cytotoxicity assays revealed that o-aminophenol derivatives 6b, 6c, 6f, 6i, and 12b exhibited moderate inhibitory effects on KB cell lines with IC50 values from 32 to 74.94 µg/mL. Compound 6i demonstrated moderate cytotoxic activity against HepG2, A549, and MCF7 cell lines, with IC50 values of 29.46, 71.29, and 80.02 µg/mL, respectively.ConclusionDesign, synthesis, antimicrobial activity, DPPH Radical Scavenging, Cytotoxic activity, Evaluation of H8 signal anomalies in certain compounds, and Single crystal X-ray diffraction analysis.
Keywords: o-nitrophenol